The development and validation of an inertial sensor for measuring cycling kinematics: a preliminary study - Evans, S. A.; Ballhause, K.; James, D. A.; Rowlands, D.; Lee, J. B. (Journal of Science and Cycling, 2021)
A biomechanical variable of interest to cyclists and cycling coaches is postural stability. A cyclist`s position on a bicycle can be easily measured in a laboratory environment using motion capture software, but is difficult to measure in the field. The focus of this paper was to identify the legitimacy of a sacrum mounted triaxial accelerometer to identify temporal acceleration magnitudes of the centre of mass (CoM) whilst cycling against a motion analysis system. To provide validation of the sensor, data was collected at the torso as cyclists pedaled at varied cadences against a motion analysis system. The effects of cycling cadence and changes to torso angle via changes to hand position revealed that wearable technology (accelerometers) provide legitimacy in the assessment of torso accelerations during cycling. The minimal variation and change in agreement between the two systems during cycling indicates the adherence method of the accelerometer was suitable.